Hybrid magnetic nanoparticle-functionalized polythiophenes and its potential as a sorbent to extract phthalates / Siti Nor Atika Baharin ... [et al.] - Baharin, Siti Nor Atika; Muhamad Sarih, Norazilawati; Mohamad, Sharifah; Shahabuddin, Syed; Said, Nur Rahimah (2019)
Magnetic polythiophene and poly-3-hexylthiophene was successfully synthesized. FTIR data suggested the presence of functionalized polythiophenes in the nanocomposites. XRD peaks confirmed the entire characteristic peak for Fe3O4 presence in all prepared nanocomposites. From the vibrating sample magnetometry hysterisis loop P3Th-coated MNPs (MNP@P3Th) established great magnetization than other nanocomposites. BET results showed decreasing trend of pore size due to addition of polymer coating. The thermograms of nanocomposite indicated that all the nanocomposites were stable up to 210 °C. The synthesized material was screened for the extraction of commercially available phthalates namely di-n-octyl phthalate (DNOP) butyl phthalate (DBP), and butyl benzyl phthalate (BBP) and P3Th-coated MNPs (MNP@P3Th) showed highest extraction concentration for all tested phthalates.